The Use of Geoboard Manipulative to Improve Elementary School Student Mathematical Problem-Solving Skills: A Classroom Action Research - Syadza Zahrotul Qolbu; Sati; Arief Hidayat Afendi (Universitas Wiralodra, 2026)
Fourth-grade students at SD Negeri 1 Pejambon showed low mathematical problem-solving skills in learning plane geometry. This condition was associated with the limited use of teaching aids, insufficient opportunities for students to construct plane shapes independently, and a lack of concrete problem-solving activities during instruction. This study aimed to describe the planning, implementation, and outcomes of using geoboard teaching aids to improve students’ mathematical problem-solving ability. The method used was Classroom Action Research (CAR) following the Kemmis and Taggart model, consisting of planning, action, observation, and reflection, conducted over two cycles involving 20 fourth-grade students. Data were collected through observation sheets (covering the teaching module, teacher performance, affective aspects, and psychomotor problem-solving skills) and essay-based tests, the analyzed using both quantitative and qualitative methods. The result showed consistent improvement across Cycles: the lesson-planning score increased from 44.44% (Pre-Cycle) to 77.77% (Cycle I) and 88.88% (Cycle II); teacher performance improved from 57.14% to 71.42% and reached 100% in Cycle II; students’ affective ability rose from 10% to 30%, with 90% of students reaching the “good” category in Cycles II; problem-solving (psychomotor) ability increased from 0% to 30% and reached 85% in Cycle II; and learning outcome mastery rose from 0% to 30% and reached 75% in Cycle II, meeting the study’s success indicator. These findings indicate that the use of geoboard teaching aids contributed to improving fourth-grade students’ mathematical problem-solving ability on the topic of plane geometry topics. This study also highlights the educational value of geoboard as concrete learning media that support elementary students in understanding geometric concepts and developing problem-solving skills.